Neutrophil-to-albumin ratio: a promising tool for CAD assessment in non-ST elevation AMI - Karasu, M.; Karaca, Y.; Yildirim, E.; Kobat, M. A.; Er, F. (Verduci Publisher, 2023)
OBJECTIVE: In the context of coronary artery disease (CAD) pathogenesis, inflammation has emerged as a critical player. This study investigates the potential of the Neutrophil-to-Albumin Ratio (NAR) as a novel bio-marker for assessing CAD severity and extension in patients suffering from acute myocardial infarction (AMI) without ST-segment elevation.PATIENTS AND METHODS: We conducted a comprehensive analysis of consecutive patient records (n = 211) from a single center, focusing on individuals diagnosed with non-ST elevation AMI. To gauge CAD severity, we employed Syntax Scores (SS) and examined their correlation with NAR, C-reactive protein-albumin ratio (CRPALB), and the systemic immune inflammation index (SII). Statistical analyses were conducted to establish associations and predictive capabilities.RESULTS: Our analysis revealed a significant correlation between NAR and Syntax Scores (r: .416, p<0.01). Notably, patients with intermediate-high SS exhibited significantly elevated NAR values com-pared to those in the low SS group [20.86+5.38 vs. 16.41+6.30 (p<0.001)]. Furthermore, NAR outper-formed CRPALB, SII, and Neutrophil Percent-to -Albu-min Ratio (NPAR) in discriminating CAD severity, as demonstrated by the Receiver Operating Character -istic (ROC) curve analysis (NAR AUC: 0.736; CRPALB AUC: 0.673; SII AUC: 0.660; NPAR AUC: 0.717).CONCLUSIONS: This study underscores the potential of NAR as a robust predictor of CAD se-verity and extension in non-ST elevation AMI pa-tients. While previous markers, such as CRPALB and SII, are advantageous, NAR's superior pre-dictive capabilities are a valuable addition to the clinician's toolkit, offering enhanced risk assess-ment for this specific patient subgroup.
Keywords: Neutrophil-to-albumin ratio; Non-ST elevated myocardial infarction; SYNTAX score